A highly selective fluorescent probe for sulfide ions based on aggregation of Cu nanocluster induced emission enhancement. Issue 8 (20th February 2015) - Li, Zenghe; Guo, Song; Lu, Chao
Abstract : S 2− ions can enhance the fluorescence of cysteine-capped Cu nanoclusters (Cu NCs) as a result of the S 2− ion-induced aggregation of the dispersed Cu NCs. In addition, a highly selective fluorescent probe was developed for the determination of H2 S from toys called "Fart Bomb". Abstract : In this study, S 2− ions were found to enhance the fluorescence of cysteine-capped Cu nanoclusters (Cu NCs). High resolution transmission electron microscopy (HRTEM), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy-energy dispersive X-ray (SEM-EDX) measurements, zeta potential and X-ray photoelectron spectroscopy (XPS) measurements demonstrated that the S 2− ion-induced aggregation of the Cu NCs contributed to the fluorescence enhancement of the dispersed Cu NCs. Based on these findings, a highly selective fluorescent probe was developed for the determination of H2 S using the S 2− ion-enhanced fluorescence of the as-prepared Cu NCs. The relative fluorescence intensity was proportional to the concentration of S 2− in the range from 0.2 to 50 μM. The detection limit (S/N = 3) was 42 nM. The proposed method has been successfully applied to determine H2 S produced from toys called "Fart Bomb" with recoveries of 97.6–101.8%. The results of the proposed method were in good agreement with those determined by a standard methylene blue method. This work is not only of importance for a better understanding of the aggregation induced emission (AIE) properties of the Cu NCs but also of great potential to find extensive biological applications for H2 S.